Leucoxenols A and B, two new phenolics from Bornean medicinal plant Syzygium leucoxylon - Kamsirah Jim Shamsudin; Chin-Soon Phan; Julius Kulip; Kishio Hatai; Charles Santhanaraju Vairappan; Takashi Kamada (2019)
The medicinal plant, Syzygium leucoxylon or commonly known as Obah found in North Borneo was considered as traditional medicine by local committee. Two new phenolics, leucoxenols A (1) and B (2) were isolated and identified as major secondary metabolites from the leaves of S. leucoxylon. Their chemical structures were elucidated based on spectroscopic data such as NMR and HRESIMS. Furthermore, these compounds were active against selected strains of fungi.